Comportamiento de la papa (solanum tuberosum l) variedad chaucha roja a la aplicación de tres tipos de abonos orgánicos en el barrio Saragocin – Parroquia Juan Montalvo - Cantón Latacunga. - De La Cruz Maigua, Luis Adrián (2020)
This research was carried out in the Saragocin neighborhood, Juan Montalvo parish, Latacunga canton, in the experimental field of Mr. Luis De La Cruz with geographical coordinates of 0056'12 '' south latitude and 78033'17 '' west longitude, The main objective was: “Behavior of the potato (solanum tuberosum L) “chaucha roja” variety to the application of three types of organic fertilizers in the Saragocin neighborhood - Juan Montalvo parish - Latacunga canton”, in order to give an organic production alternative to the farmers. The objectives were: to evaluate the behavior of the “chaucha roja”potato to the application of three types of organic fertilizers; to determine the organic fertilizer and the best dose that act on the cultivation of “chaucha roja” potato, it aimed a completely randomized block design (DBCA) with 3 repetitions, for the treatments under study we obtained: 10 treatments and 3 repetitions, resulting in a total of 30 experimental units. An experimental model of completely randomized block design was applied, applying the 5% Tukey Test for the sources of variation that present significant differences, the statistical analysis was performed using 2018 Infostat. Three ranges of significance were identified in the experimental field giving as the best organic fertilizer to (Luckysoil + 2 lb) with an average of 34.50 tubers / plant being in the first range of significance, then secondly, the fertilizer (fertiplus + 2 lb) is located with an average of 25.32 tubers / plant and in the last range of significance was located (ecua bonaza + 2 lb) with an average of 25.31 tubers / plant, therefore, in the investigation it was determined that the best Organic fertilizer was Luckysoli allowing the plant to develop and obtain a good ripening of Tubers.